EUS-Guided Bile Duct Drainage (EUBD) in 95 Patients - Will, U.; Fueldner, F.; Kern, C.; Meyer, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: Bile duct stenting during ERCP has long been established as the gold standard for the treatment of biliary obstruction. However, when the ampulla cannot be reached or bile duct cannulation fails, percutaneous or surgical drainage is performed. The study aimed to investigate the feasibility and long-term outcome of a potential alternative intervention, EUS-guided transluminal biliary drainage (EUBD), in a representative number of patients.Materials and Methods: All patients undergoing EUBD were included in a prospectively collected single-center database over a 10-year period. Feasibility was characterized by technical and clinical success, including long-term follow-up data.Results: From IV/2002 – XI/2012, 10 832 EUS and 8756 ERCP procedures were performed. Simultaneously, 223 PTCD and 95 EUBD were performed. Cholangiography was achieved in 93/95 patients (97.9 %). However, in one patient stone extraction was executed by means of the rendezvous technique. Therefore, drainage was not necessary. Intention to treat with EUS-guided drainage was given in 80/94 patients (86.9 %) using different techniques depending on anatomical variations and requirements. The cause of bile duct obstruction could not be cured in 77 patients (malignancy). In 18 patients, a benign (n = 15) or unknown etiology (n = 3) of bile duct stenosis was found. The complication rate was 15.7 % (mortality, 1.1 %; n = 1/95). The follow-up ranged from 3 – 60 months with reintervention in 3 patients.Conclusion: EUBD is a promising therapy for bile duct obstruction in patients predominantly with malignant diseases. Using EUBD, an excellent interventional approach is available for long-term internal drainage to prevent percutaneous drainage (PTCD). EUS-guided drainage is challenging and needs extraordinary interventional expertise, preferentially in tertiary gastroenterological and endoscopic centers.
Keywords: EUS-guided bile duct drainage (EUBD); cholestasis; bile duct obstruction; interventional EUS; cholangiography